Assessment of satisfaction of using socially marketed health consumables at government settings among beneficiaries in a rural area of Hooghly District, West Bengal - Aditi Sur; Bobby Paul; Lina Bandyopadhyay; Monalisha Sahu; Rivu Basu; Ankush Banerjee (Journal of Family Medicine and Primary Care)
Introduction: India is committed to achieving universal health care for all by 2030. The objective of social marketing is to promote public health and its goal is to improve health for all, but there are some challenges like irregular availability, quality issue, inadequacy of marketing causes under- utilization of the government supplied health consumables. Objectives: Present study aims to find out the usage pattern and assess the perceived satisfaction level of beneficiaries of using various socially marketed health consumables at government settings and explore the perception of healthcare personnel regarding barriers to its usage in a rural area of India. Materials and Methods: A community-based, Mixed-Methods study (Convergent parallel design) was done in the service area of the Rural Health Unit and Training Centre (RHU&TC), Singur of Hooghly district, West Bengal, between January 2023 and December 2023, where the quantitative component was carried out by face-to-face interview among 150 beneficiary household respondents selected by two-stage cluster sampling; and qualitative component was done by 4 Key informant interviews (KII) among healthcare personnel (medical officer, public health nurse, pharmacist). Statistical data were analyzed by descriptive statistics using SPSS 16 version and Microsoft Excel for the quantitative part, and thematic analysis was done for the qualitative part. Institutional Ethics Committee clearance was obtained. Results: Ever use of government-supplied contraceptives like Chhaya (Ormeloxifene), Antara (Injectable contraceptive), emergency contraceptive pills, and intrauterine contraceptive devices (IUCD) was done by only 15.3%, 10.7%, 7.3%, 32% of eligible beneficiary households, respectively. The major reasons cited for irregular use were unawareness of availability of the products (Chhaya = 76.3%, Antara = 64.9%, EC pills = 46.7%), poor faith regarding quality (Male condom = 40%, Generic medicines = 70%), inadequate promotion (IUCD = 53.9%). The majority of users of male condoms (90%), IFA tablets (52.9%), ORS (51.1%), and generic medicines (55.7%) were not satisfied after using those products. Key informant interviews among healthcare personnel revealed avoidance of using modern contraceptive methods and frequent unavailability of some socially marketed health consumables were the predominant causes of reduced uptake of those products by beneficiaries. Conclusions: Proper social marketing strategies, adequate promotion, regular awareness campaigns, and tailored training of field healthcare workers are required to improve the acceptability, availability, and marketing of these health consumables.